Connecting Health and Humans - Saranto (IOS Press, 2013)
The proceedings of the 10th International Nursing Informatics Congress (NI2009) offers a wide range of scientific knowledge to be disseminated among nurses, administrators, physicians or informaticians irrespective of whether they are clinicians, teachers, researchers or students. The variation of papers follow the advances in health information technology, although certain important topics such as ethics, education, management and clinical practice applications remain. The proceedings follows the ten themes of the conference programme: clinical workflow and human interface; consumer health informatics and personal health records; health information technology; terminology, standards and NMDS’s; patient preferences and quality of care; patient safety; evidence based practice and decision support; consumer and professional education; strategies and methods for HIT training and national eHealth initiatives across the globe.